2021
DOI: 10.3389/fcvm.2021.736466
|View full text |Cite
|
Sign up to set email alerts
|

Similar Inflammatory Biomarkers Reflect Different Platelet Reactivity in Percutaneous Coronary Intervention Patients Treated With Clopidogrel: A Large-Sample Study From China

Abstract: Background: Platelet reactivity is closely associated with adverse events in percutaneous coronary intervention (PCI) patients. Inflammation plays a crucial role in the development of coronary heart disease (CHD).Aim: To investigate the association of inflammatory biomarkers such as leukocyte count and high-sensitivity C reactive proteins (hs-CRP) with platelet reactivity in PCI patients treated with clopidogrel.Method: We examined 10,724 consecutive PCI patients in Fuwai hospital from January 2013 to December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
6
2
Order By: Relevance
“…Additionally, reduction of residual inflammation by colchicine therapy may impact platelet reactivity, as elevated levels of inflammatory markers like hs-CRP and fibrinogen have been linked to increased platelet reactivity ( 39 , 40 ). Although the present study did not demonstrate a correlation between hs-CRP and PRU measures, a previous study demonstrated that higher hs-CRP levels were associated with greater platelet reactivity in PCI patients treated with clopidogrel ( 41 ). Therefore, the current findings suggest that ticagrelor or prasugrel might be less susceptible to the pro-aggregatory effects of inflammation compared to clopidogrel.…”
Section: Discussioncontrasting
confidence: 98%
“…Additionally, reduction of residual inflammation by colchicine therapy may impact platelet reactivity, as elevated levels of inflammatory markers like hs-CRP and fibrinogen have been linked to increased platelet reactivity ( 39 , 40 ). Although the present study did not demonstrate a correlation between hs-CRP and PRU measures, a previous study demonstrated that higher hs-CRP levels were associated with greater platelet reactivity in PCI patients treated with clopidogrel ( 41 ). Therefore, the current findings suggest that ticagrelor or prasugrel might be less susceptible to the pro-aggregatory effects of inflammation compared to clopidogrel.…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, it is essential to investigate other potential risk factors of HRPR. Contemporary biomedical literature supports that inflammation may play an important role in the progression of atherosclerosis and thrombosis initiated by rupture of atherosclerotic plaques, and a previous study found that inflammatory biomarkers could influence ADP-induced platelet aggregation assessed by platelet function test during clopidogrel treatment (31). As a major participant in innate immune responses and inflammatory processes, the complement system is also involved in the regulation of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that elevated concentrations of these cardiovascular risk biomarkers are associated with many pathological processes; however, the mechanism of how D-dimer, hs-CRP, and Lp(a) predict mortality remains unclear. Previous studies showed that elevated D-dimer was related to thrombosis, 24 plaque necrosis, 24 and infection, 25 whereas elevated hs-CRP was related to high platelet reactivity, 26 smooth muscle cell proliferation, human macrophage polarization, 27 and thromboxane activity. 27 Furthermore, elevated Lp(a) was related to endothelial damage, 28 inflammatory response, 29 and fibrinolytic inhibition.…”
Section: Discussionmentioning
confidence: 99%